Microbial diversity and activity in seafloor brine lake sediments (Alaminos Canyon block 601, Gulf of Mexico). Issue 5 (21st July 2016) - Crespo‐Medina, M.; Bowles, M. W.; Samarkin, V. A.; Hunter, K. S.; Joye, S. B.
Abstract: The microbial communities thriving in deep‐sea brines are sustained largely by energy rich substrates supplied through active seepage. Geochemical, microbial activity, and microbial community composition data from different habitats at a Gulf of Mexico brine lake in Alaminos Canyon revealed habitat‐linked variability in geochemistry that in turn drove patterns in microbial community composition and activity. The bottom of the brine lake was the most geochemically extreme (highest salinity and nutrient concentrations) habitat and its microbial community exhibited the highest diversity and richness indices. The habitat at the upper halocline of the lake hosted the highest rates of sulfate reduction and methane oxidation, and the largest inventories of dissolved inorganic carbon, particulate organic carbon, and hydrogen sulfide. Statistical analyses indicated a significant positive correlation between the bacterial and archaeal diversity in the bottom brine sample and NH 4 + inventories. Other environmental factors with positive correlation with microbial diversity indices were DOC, H2 S, and DIC concentrations. The geochemical regime of different sites within this deep seafloor extreme environment exerts a clear selective force on microbial communities and on patterns of microbial activity.